Back Cover: From Quantum Rabi Model To Jaynes–Cummings Model: Symmetry‐Breaking Quantum Phase Transitions, Symmetry‐Protected Topological Transitions and Multicriticality (Adv. Quantum Technol. 1/2022). Issue 1 (4th January 2022) - Ying, Zu‐Jian
Abstract : Traditionally topological phase transitions lie in condensed matter, are they possible to occur in a single‐qubit system? Are universality and diversity foes or friends? In article number 2100088, Zu‐Jian Ying illuminates a fine‐structure phase diagram for the anisotropic quantum Rabi model with a finding of series transitions, multicriticality, and quadruple points emerging beyond the conventional picture. The emerging transitions are found to be topological transitions. The topological feature of the wave function provides a new universality classification reformed among the diversity in the breaking down of the conventional universality.